Cardiovascular publications in 2013 in Turkey advanced in quantity alone - Altan Onat (KARE Publishing, 2014)
Turkey's institutions in cardiovascular medicine were evaluated regarding publication output in 2013 based on data available in the Web of Science. Only articles in fulltext and reviews appearing in source publications covered by the Science Citation Index proper were included. A fractional count system was used for items published jointly with a foreign or a non-cardiological Turkish institution. Turkey's publications increased numerically to 268, and its global share from 4.3 to 6.0 per mille, yet only to the level of 2001. Articles originating from adult cardiology numbered 188 (70%), while cardiovascular surgery and pediatric cardiology contributed 15% each. Three hospitals affiliated with the Ministry of Health (Kartal Koşuyolu, M. Akif Ersoy and Turkiye Yüksek İhtisas Hastanesi) and the cardiology departments of the medical faculties of Başkent, Hacettepe and Ege Universities ranked highest, each generating 7-15 papers. The median impact factor remained similar to the preceding year, at 1.52 (interquartile range 1.20 - 2.31). The undertaking of promotional and supportive measures by the central authorities regarding the conspicuous decline in Turkey's medical research output is long overdue.